Antiprotozoal Aminosteroids from Pachysandra terminalis - Lizanne Schäfer; Monica Cal; Marcel Kaiser; Pascal Mäser; Thomas J. Schmidt (Molecules)
Trypanosoma brucei rhodesiense (Tbr) and Plasmodium falciparum (Pf) are protozoan parasites that cause severe diseases, namely, Human African Trypanosomiasis (HAT) and Malaria. Due to limited treatment options, there is an urgent need for new antiprotozoal drugs. Pachysandra terminalis (P. terminalis), a plant belonging to the family Buxaceae, is known as a rich source of aminosteroid alkaloids, and a previous study of our working group already showed that the alkaloid-enriched fraction of P. terminalis aerial parts showed promising activity against protozoan parasites. In the present study, the alkaloid-enriched fraction obtained from a 75% ethanol extract of aerial parts was separated to isolate a chemically diverse array of Pachysandra alkaloids for assessment of their antiprotozoal activity and later structure–activity studies. This work yielded a new megastigmane alkaloid (1), 7 new aminosteroids (2, 7, 16, 17, 18, 19, 20), along with 10 known aminosteroids (3–5, 8, 10–15) and 2 artifacts (6, 9) that were formed during the isolation process. The structures were elucidated by UHPLC/+ESI-QqTOF-MS/MS, as well as extensive 1- and 2D-NMR measurements. The extract and its fractions, as well as the isolated compounds, were tested in vitro against Tbr and Pf, as well as cytotoxicity against mammalian cells (L6 cell line). The activity (IC50 values) of the isolated alkaloids ranged between 0.11 and 26 µM (Tbr) and 0.39 and 80 µM (Pf). 3α,4α-diapachysanaximine A (7) showed the highest activity against Tbr (IC50 = 0.11 µM) with a selectivity index (SI) of 133 and was also quite active against Pf with IC50 = 0.63 µM (SI = 23). This compound is, therefore, a promising new antiprotozoal target for further investigations.